Analysis of critical causes of transaction cost escalation in public sector construction projects - Zaigham Ali; Ifzal Ahmad; Zahid Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
Although transaction costs (TCs) that affect the total project costs are a common phenomenon in the Pakistani construction industry, the causes that escalate the TCs are ambiguous, and public sector organizations are unable to manage these causes efficiently. To investigate the causes of escalation of TCs in public sector construction projects, a total of 30 causes were first identified through a review of the literature and factor analysis was employed for further analysis. The semi-structured interviews were conducted with 8 professionals from the construction industry in Pakistan. The primary data used to prioritize the causes of escalation of TCs were collected from survey questionnaires in which causes such as inadequate investigation, an unclear work scope, project complexity and incomplete design and specification ranked the highest. Finally, factor analysis was used and identified 5 major underlying dimensions of the causes, namely, the procurement and contracting management, the contractor relationship management, the project external environment, managing project finance and the project transaction environment. The contribution of this research lies in the identification and examination of the underlying causes of TC escalation, as discerned by the industry professionals. All factors are important, but in the local context, soft aspects (contract relationship) and hard aspects (financial management) are additional factors perceived by the experienced professional in overcoming TC escalation issues. This could be a point of reference in the public sector construction industries of developing countries, which are characterized by their unique economic and social systems.
Keywords: 330; construction projects; project complexity; transaction environment; transaction cost; project procurement; Pakistan